Pengaruh Simulasi Bisnis terhadap Peningkatan Pemahaman Kewirausahaan Siswa Kelas XI di MA NW Ar-Rahmaniyah - Abdurrahim, Abdurrahim (ARZUSIN, 2024)
The limitations of interactive and contextual learning methods make it difficult for students to apply entrepreneurship concepts in real-life situations. This study aims to determine the influence of business simulation on improving entrepreneurship understanding among 11th-grade students at MA NW Ar-Rahmaniyah Senyiur. This research employs a quantitative approach with an experimental method, involving 45 students from 11th grade IPA and IPS classes. Data collection techniques in this study include observation and questionnaires in the form of pre-tests and post-tests to measure changes in students' understanding, which are then analyzed using a t-test. The results show a significant improvement in students' understanding of entrepreneurship, particularly in terms of creativity, adaptability, teamwork, and risk-taking. This improvement reflects the positive impact of business simulation in developing entrepreneurial skills and highlights its potential as an effective educational tool. By preparing students to think like entrepreneurs, this approach can encourage them to become job creators in the future, thereby helping to address broader socio-economic challenges.